Comparative studies of nickel doping effects at A and B sites of BaTiO3 ceramics on their crystal structures and dielectric and ferroelectric properties. Issue 17 (1st December 2017) - Fu, Chenjie; Chen, Nan; Du, Guoping
Abstract: Effects of Ni 2+ doping at A and B sites of BaTiO3 ceramics on the crystal structures, microstructures, chemical bonding characteristics and dielectric and ferroelectric properties were studied. Both the A-site doped Ba1−x Nix TiO3 and B-site doped BaTi1−x Nix O3 ceramics ( x = 0, 0.01, 0.03, 0.05, 0.08 and 0.10) were prepared using the solid state reaction method at 1300 °C. For Ni 2+ doping at A sites, no change in the crystal structure of Ba1−x Nix TiO3 was observed. The Ba1−x Nix TiO3 ceramics remained to be of tetragonal structure, but their tetragonality consistently decreased with x . For Ni 2+ doping at B sites, a change in the crystal structure from tetragonal to hexagonal was observed for the BaTi1−x Nix O3 ceramics. The hexagonal structure started to appear when x = 0.03, and BaTi1−x Nix O3 ceramics completely transformed from tetragonal to hexagonal structure when x =0.08. Ni 2+ doping introduced more oxygen vacancies to Ba1−x Nix TiO3 and BaTi1−x Nix O3, and the latter had higher concentration of oxygen vacancies. It was found that Ni 2+ doping, either at A or B sites, strongly decreased their dielectric and ferroelectric properties. The Ba1−x Nix TiO3 ceramics remained to be ferroelectric for x up to 0.10, although it was weak, while the BaTi1−x Nix O3 ceramics became paraelectric when x = 0.03. The Ba1−x Nix TiO3 ceramics exhibited higher dielectric constant than the BaTi1−x Nix O3 .